2021
DOI: 10.1111/jfpp.15442
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atmospheric cold plasma (ACP) on maintaining bolti fish (Tilapia nilotica) freshness and quality criteria during cold storing

Abstract: Atmospheric cold plasma (ACP) is a novel non-thermal technique that provides the ability to denaturate enzymes without damaging main components. The first purpose of this research is to evaluate the impact of ACP produced via dielectric barrier discharge (DBD) on endogenous enzymatic activity and tilapia quality characteristics.How to cite this article: Mohamed EE, Younis ER, Mohamed EA. Impact of atmospheric cold plasma (ACP) on maintaining bolti fish (Tilapia nilotica) freshness and quality criteria during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
(65 reference statements)
2
17
0
Order By: Relevance
“…Therefore, the differences in color value between the CAP-treated sample and control samples could be due to the destruction of endogenous enzymes including peroxidases during the CAP treatment, which slows down the oxidation of fish, thereby effectively maintaining the color [ 44 ]. Our results are in agreement with Mohamed et al (2021), who reported significant stability in the lightness and whiteness of Nile tilapia fish subjected to dielectric barrier discharge–CAP (DBD–CAP) under 60 kV for 4 min [ 43 ]. However, in another study, no significant differences in color parameters were found between the plasma-treated chicken breasts and untreated samples [ 11 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the differences in color value between the CAP-treated sample and control samples could be due to the destruction of endogenous enzymes including peroxidases during the CAP treatment, which slows down the oxidation of fish, thereby effectively maintaining the color [ 44 ]. Our results are in agreement with Mohamed et al (2021), who reported significant stability in the lightness and whiteness of Nile tilapia fish subjected to dielectric barrier discharge–CAP (DBD–CAP) under 60 kV for 4 min [ 43 ]. However, in another study, no significant differences in color parameters were found between the plasma-treated chicken breasts and untreated samples [ 11 ].…”
Section: Resultssupporting
confidence: 93%
“…These findings revealed that the CAP treatment could maintain the color of the hairtail during cold storage at g at 4 ± 1 °C. While the color of fish is usually influenced by pigment levels and muscle structural properties, protein oxidation also leads to coloring loss in fish tissues [ 43 ]. Therefore, the differences in color value between the CAP-treated sample and control samples could be due to the destruction of endogenous enzymes including peroxidases during the CAP treatment, which slows down the oxidation of fish, thereby effectively maintaining the color [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies on cold plasma application in aquatic products have become more prevalent and have focused primarily on the quality changes during storage after treatment. Mohamed et al [ 15 ] studied the effects of dielectric barrier discharge (DBD) cold plasma voltages and treatment time on the quality of tilapia during refrigerator storage and found that the cold plasma treatment had a significant effect on the enzyme activities and the number of microorganisms; the shelf-life was extended to 10 days when samples were treated at 60 kV for 4 min. Albertos et al [ 16 ] investigated the effect of atmospheric cold plasma on the microbial and quality parameters of mackerel fillets treated with different voltages and times.…”
Section: Introductionmentioning
confidence: 99%
“…Another study with fish is by Mohamed et al [ 27 ], which focuses on tilapia quality characteristics and endogenous enzyme activity, but also counts spoilage bacteria through total viable cell count (TVC). The results of this study revealed that the duration and voltage of therapy had a significant impact on enzyme activities, TVC and other measured parameters, and thus the ideal treatment parameters for tilapia were found to be 60 kV for 4 min.…”
Section: Application Of Dbd In Food For Decontaminationmentioning
confidence: 99%